2009
DOI: 10.1177/0748233709354554
|View full text |Cite
|
Sign up to set email alerts
|

Toxic effects of T-2 toxin on reproductive system in male mice

Abstract: The present study was conducted to evaluate the effects of T-2 toxin on semen quality, fertility and serum testosterone concentration in mice. Adult male mice were mated with sexually mature untreated female mice after being exposed to intraperitoneal injection of T-2 toxin at 0, 5, 10 or 15 mg/kg body weight daily for 7 successive days. Semen quality, serum testosterone concentration and fertility of treated mice were assessed. The results showed that the number of abnormal spermatozoa increased significantly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(9 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…For males, the maturation of sexual organs and the emergence of sexual characteristics are directly influenced by TM3 cells. Yang’s experiment has demonstrated that T-2 toxin has negative effects on male fertility and other reproductive pathologies [ 24 ]. More research has proven that TM3 cells are influenced by T-2 toxin in a dose-dependent manner and has revealed the mechanisms of cytotoxicity [ 25 , 26 , 27 , 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…For males, the maturation of sexual organs and the emergence of sexual characteristics are directly influenced by TM3 cells. Yang’s experiment has demonstrated that T-2 toxin has negative effects on male fertility and other reproductive pathologies [ 24 ]. More research has proven that TM3 cells are influenced by T-2 toxin in a dose-dependent manner and has revealed the mechanisms of cytotoxicity [ 25 , 26 , 27 , 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…An in vivo study that aimed to evaluate the toxic effect of T-2 on a reproductive system revealed that this toxin affects male mice fertility [66]. The results showed that the number of live spermatozoa decreased significantly.…”
Section: Reproductive Systemmentioning
confidence: 99%
“…Furthermore, intramuscular injection of increasing doses of AFB1 (10, 20, or 50 µg/kg BW) in adult rats resulted in the reduction of reproductive organ weights, daily sperm production, epididymal sperm count, viable sperm, and motile sperm [138]. Similarly, the T-2 toxin showed an increase in the number of abnormal spermatozoa and a decrease in spermatozoa count in adult male mice, and these resulted in low pregnancy rates and high fetal resorption after exposure to 10 and 15 mg/kg BW T-2 toxin [144].…”
Section: Spermatogenesis: a Complex And Delicate Processmentioning
confidence: 99%
“…Although the study of epigenetics initially focused on the role it plays as a regulatory system, recent landmark observations have linked environmental exposure and gene–environment interactions to a significant proportion of human malignancies. The Dutch Hunger Winter remains a classic example of such environmental interactions where pregnant women during the famine period gave birth to children and future generations who exhibited higher rates of obesity, diabetes, schizophrenia, and mortality upon adulthood [144]. The latter set forward the study of transgenerational epigenetic inheritance, where the germline undergoes epigenetic modifications inherited by future generations despite the extensive epigenetic resetting event, with epigenetic tags on some loci associated with metabolic and neurological disorders that can escape this reprogramming [160].…”
Section: Epigenetic Implicationsmentioning
confidence: 99%